Comparison of risk of malignancy indices in the preoperative evaluation of adnexal masses - Hegaab, Hassan Mansour; El Sokkary, Hossam; Abo Elwafa, Reham; Elzeity, Eman Salem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: An adnexal mass patient is a common cause of hospital admission. The differentiation between malignant and benign cases is an important step in the management of such patients. The risk of malignancy index (RMI) is a simple scoring system depend on ultrasound data, menopausal status and serum concentrations of CA-125 tumor marker and has a great value in differentiation between benign and malignant adnexal masses. 4 different types of risk of malignancy index are created. The objective of the study was to compare the diagnostic performance of the four malignancy risk indices in differentiating benign and malignant ovarian tumors. Methods: This prospective study was performed on 60 patients with an adnexal mass confirmed on vaginal ultrasound. Results: There was statistical significance difference between the 4 types of RMI in benign and malignant groups. RMI 1, RMI 2, and RMI 3 had nearly the same area under the ROC curve; however, at the cut-off of>58.41, RMI 3 was more sensitive and less specific than RMI 1 or RMI 2. The RMI 2 was the most specific in predicting malignancy in terms of area under the curve; however, there was no statistically significant difference in performance of RMI 2 and 4 in malignant group. Conclusions: RMI 1, RMI 2, and RMI 3 had nearly the same area under the ROC curve; however, at the cut-off of >58.41, RMI 3 was more sensitive and less specific than RMI 1 or RMI 2, on the other hand the most specific was RMI 2 more than the other 3 RMIs.